Equivariant Dynamical Systems - Ertinger, Z. (Radioengineering Society, 1995)
Our aim is to present some aspects of the mathematical theory of strange behaviour of nonlinear systems, especially of systems with symmetry. Proofs are emitted, the interested reader is advised to references. Our presentation is inevitably selective. We focus on parts of the theory with possible applications to electronic circuits and systems which may display chaotic behaviour.
Keywords: nonlinear systems; systems with symmetry